K-Pop and Consumerism Culture: A Bibliometric Analysis Review - Arriyuka, Oshima Vicky; Yumitro, Gonda (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research discusses consumerism behavior among Korean Pop (K-Pop) fans as an impact of the Hallyu Wave. This trend, rich in Korean culture, has become global and developed rapidly. The research method applied in this study is a Bibliometric Analysis review, using more than 50 scientific articles sourced from the Scopus database, which were then analyzed and visualized using Vosviewer, Nvivo, and Mendeley applications. The study results reveal that consumer behavior among K-pop fans is increasing and is driven by social media as a form of technological advancement. Advanced technology makes it easier and faster for things to spread, including the Hallyu Wave. This has made K-pop culture increasingly beloved worldwide. This phenomenon can influence people's lives globally, especially in a consumerist culture. This culture or phenomenon's entry also impacts K-pop fans positively and negatively. The article has a limitation in that the scientific data used is sourced only from the Scopus database, which means the findings of this study cannot be described comprehensively.